2021
DOI: 10.1016/j.radonc.2021.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Study of relationship between dose, LET and the risk of brain necrosis after proton therapy for skull base tumors

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…The volume of the AE regions was increased greatly from 2.81 to 22 cm 3 in 11 months, which indicated that more than 90% of the voxels in the AE regions were due to the biological expansion if the AE regions were contoured in the last follow-up CT images, that is, the "noise" (voxels damaged by the biological expansion) was significantly higher than the "signal" (voxels damaged by dosimetric effect, i.e., dose and LET) itself. Similar phenomenon was also reported in other voxel-based analyses 58,59,83 to investigate dosimetric effects upon AEs. If we want to understand the impact of dosimetric effects upon AE initialization, it is critical to mitigate the impact from such biological processes.…”
Section: Ae Regions May Expand Over Time Due To Biological Effectssupporting
confidence: 86%
See 2 more Smart Citations
“…The volume of the AE regions was increased greatly from 2.81 to 22 cm 3 in 11 months, which indicated that more than 90% of the voxels in the AE regions were due to the biological expansion if the AE regions were contoured in the last follow-up CT images, that is, the "noise" (voxels damaged by the biological expansion) was significantly higher than the "signal" (voxels damaged by dosimetric effect, i.e., dose and LET) itself. Similar phenomenon was also reported in other voxel-based analyses 58,59,83 to investigate dosimetric effects upon AEs. If we want to understand the impact of dosimetric effects upon AE initialization, it is critical to mitigate the impact from such biological processes.…”
Section: Ae Regions May Expand Over Time Due To Biological Effectssupporting
confidence: 86%
“…This could be one of the reasons that inconsistent conclusions have been derived in different AE studies in proton therapy. 50,54,78,83 Seed spot analysis is in-line with the concept of "lesion origin" proposed by Bahn et al 54 In their study, they grounded their analysis by stating the hypothesis that the AE region "originates from a single spot of tissue breakdown from which it expands, possibly in a nonisotropic fashion, because of cascading deteriorative reactions." Seed spot analysis resembles the patchbased methods in medical imaging analysis in finding spatial clusters of voxels that possess similar characteristics or patterns in a limited number of patients, 85 but it is from a dosimetry perspective.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…A further strength of the current study is that the analysis was performed on a voxelwise level instead of relying on crude contours of organs or subregions allowing for a deeper understanding and evaluation of the lesions. Table 3 summarizes results from other investigations of RICE after PRT [18,19,[21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore in LETopt, LET d values above a set LET d level were only penalized in voxels with a dose above a user-specified threshold. Clinical follow-up studies consistently reported LET d values around 2.5 keV/µm and D 1.1 above 40 Gy(RBE) in radiation-induced image change areas after cranial proton therapy [ 8 , 12 , 13 , 29 31 ]. Accordingly, here, LET d values above 2.5 keV/µm were penalized in critical OAR but only in voxels with D 1.1 above 40 Gy(RBE).…”
Section: Methodsmentioning
confidence: 99%